Оптимизация доз облучения аварийных работников на основе метода математического моделирования - Kryuk Юлианна (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The analysis of modern approaches to the implementation of the basic principles of radiation protection and safety of employees in the normal and emergency management of the source was done. The necessity of finding cost-effective methods to reduce the likely doses of emergency personnel was shown. The possibility of using mathematical modeling method for routing optimization of radiation protection was examined. It was shown that the proposed method allows reducing the estimated radiation dose to 20% without significant economic costs.